2015
DOI: 10.1103/physrevd.91.014508
|View full text |Cite
|
Sign up to set email alerts
|

Critical endpoint of the finite temperature phase transition for three flavor QCD

Abstract: We investigate the critical endpoint of finite temperature phase transition of N f ¼ 3 QCD at zero chemical potential. We employ the renormalization-group improved Iwasaki gauge action and nonperturbatively OðaÞ-improved Wilson-clover fermion action. The critical endpoint is determined by using the intersection point of kurtosis for the temporal size Our current estimation of ffiffiffiffi t 0 p m PS;E in the continuum limit is about 25% smaller than the SU(3) symmetric point.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 29 publications
8
66
0
Order By: Relevance
“…The general trend is: the more one approaches the continuum limit, by decreasing the lattice spacing or by improving the action, the softer the transition, and the lighter the critical "pion" is. The most remarkable case is that of [10]: using a stout-improved action with staggered fermions on an N t = 4 lattice, no sign of a first-order transition was found, [8] and non-perturbatively improved Wilson fermions [5]. The N t = 4 and 6 Wilson fermion data would mistakenly suggest small lattice artifacts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The general trend is: the more one approaches the continuum limit, by decreasing the lattice spacing or by improving the action, the softer the transition, and the lighter the critical "pion" is. The most remarkable case is that of [10]: using a stout-improved action with staggered fermions on an N t = 4 lattice, no sign of a first-order transition was found, [8] and non-perturbatively improved Wilson fermions [5]. The N t = 4 and 6 Wilson fermion data would mistakenly suggest small lattice artifacts.…”
mentioning
confidence: 99%
“…In contrast, with Wilson fermions Ref. [5] finds a critical "pion" mass of about 300 MeV after extrapolating from N t = 6 and 8.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was first published at Lattice 2010 [1] and has been used by several groups: the QCDSF-UKQCD collaboration [2][3][4][5][6][7], CSSM [6][7][8][9], Japanese finite density [10,11] and finite temperature [12] projects, and the RQCD collaboration [13].…”
Section: Introductionmentioning
confidence: 99%
“…[8] reported a relatively heavy critical mass. Our recent study [9], while confirming a large value for coarse lattice spacings, suggested that the critical mass appears to be smaller for finer lattice spacings. This implies that removal of scaling violation is crucial for Wilson-type fermion action as well.…”
Section: Introductionmentioning
confidence: 90%